Study on the evaluation of fault stability and its influencing factors in rongchang area - Shaowei Huo; Shaowei Huo; Youjun Tang; Zhuliang Qian; Xingqiang Feng; Xingqiang Feng; Yahao Mei; Yahao Mei (Frontiers in Earth Science)
The Rongchang area, boasting abundant shale gas resources, has emerged as a pivotal region for reserve augmentation and production increase. Influenced by the Huayingshan Fault Zone, a multitude of faults have developed within this area. During the shale gas development process, the injection of high - pressure fluids and hydraulic fracturing operations are likely to trigger alterations in the stress field adjacent to the faults, thereby exerting an impact on the fault stability. Through the comprehensive utilization of geological and geophysical data, this research delves deeply into the contemporary in - situ stress environment of the Wufeng - Longmaxi Formation in the study area. In combination with the Coulomb criterion, it assesses the stability of the faults in the study area and probes into the factors influencing fault stability. The findings reveal that the contemporary in - situ stress relationship in the study area is characterized by SHmax > Sv > Shmin, placing it in a strike - slip stress environment. The evaluation of fault stability demonstrates that the faults in the western and southern parts of the study area exhibit poor stability, while those in the northeastern part possess relatively better stability. Moreover, it has been discovered that there exist disparities in stability along the same fault. There is a necessity to establish a fault model to further explore the stability factors. The results indicate that in the study area, faults with a dip angle of occurrence less than 10°, as well as those with an azimuth angle less than 30° and a dip angle greater than 60°, enjoy good stability. Conversely, for faults with an azimuth angle exceeding 50°, their stability diminishes as the dip angle increases. When the azimuth angle reaches 70° and the dip angle is greater than 70°, the stability is rather poor. This clearly indicates that the occurrence of faults stands as a crucial factor influencing fault stability. As the pore pressure rises, the range of azimuth angles and dip angles of potentially unstable faults gradually expands, signifying that pore pressure is also an essential factor affecting fault stability. This research furnishes a theoretical foundation for circumventing potential risks and attaining efficient development during the shale gas development process.